Three-year prevalence of measles antibody seropositivity at a tertiary care hospital in Turkey - Ayfer Bakir; Muhammed Furkan Kurkcu; Mustafa Guney; Fatime Yildiz; Mehmet Tevfik Yavuz (National Scientific Medical Center, 2021)
Objective: Measles virus is an unsegmented, single-stranded and negative-polarized RNA virus belonging to Morbillivirus genus in Paramyxoviridae family in the order of Mononegavirales. This study aimed to evaluate measles antibody seropositivity proportions in different age groups from different geographical regions within three years.  Material and methods: This retrospective study, IgM and IgG antibodies specific to measles were detected in serum samples with enzyme immunoassay method. Measles IgG antibody seroprevalence was calculated by correlating all data with demographic variables. Results: Median age of patients included in the study was 27 years and while 352 (44.4%) were male. Seropositivity rate of measles IgG antibody was 87.1%. Seropositivity in the age group of 0-18 was 77.7%  (p = 0.002). IgG seropositivity rates were 82.8%, 88.8% and 90.7% between 2017 and 2019 respectively (p = 0.05).  Seropositivity rate of IgM antibody in all cases was 11.1% and the highest rate was detected in the age group of 0-18 (13.5%) (p = 0.09). IgM antibody seropositivity rate was determined most in the winter months (23.8%) (p < 0.001). While measles IgM positivities were 10.6% and 21.1% in Turkish and foreign patients respectively IgG positivities were 86.9% and 92.3% (p = 0.32, p = 1.00 respectively). Measles IgG seropositivity was the highest in patients living in Aegean region (96.8%).  Conclusions: In conclusion, measles IgG seropositivity was 87.1% in this study. This rate was lower in pediatric age group. Increasing regional seroprevalence studies may help enhancement efforts on vaccination program to reach and sustain high population immunity.